The Citizen's Wage : The State and the Elderly in Canada, 1900-1951 - Snell, James G. (Book collections on Project MUSE., 1996)
Although we inevitably grow old, the social, cultural, and economic characteristics associated with aging are neither natural nor inevitable. James Snell brings a historian's perspective to the problems of aging and the discourse that surrounds it, a discourse that affects both public policy and the way we think about older people.